NODIRABEGIM – A SOURCE OF INSPIRATION FOR SINCERITY AND LOYALTY - Shahnoza Kamoliddin qizi Ortiqboyeva (PEDAGOGS, 2025)
Abstract: This article explores the multifaceted life and literary legacy of Nodirabegim, a poetess who sang of loyalty and elegance. It also highlights her significant reforms in state governance and her role as a cultural and intellectual leader.